Peningkatan Pengetahuan Guru, Siswa, dan Pengelola Kantin SMA Negeri 1 Muara Gembong Bekasi dalam Membuat Label Kemasan Pangan: Increasing the Knowledge of Teachers, Students and Canteen Managers at SMA Negeri 1 Muara Gembong Bekasi in Making Food Packaging Labels - Alsuhendra, Alsuhendra; Ridawati, Ridawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This Community Service activity was conducted at SMAN 1 Muara Gembong, Bekasi on July 31, 2024. The targets or participants of this activity were teachers, students and canteen managers with a total of 30 people. The activity was carried out in the meeting room of SMAN 1 Muara Gembong. This activity aims to increase the target's knowledge and skills in making packaging for processed food products, especially in making packaging labels. In this activity, data on knowledge about food product packaging and labels was collected, both before (pre-test) and after the discussion activity (post-test). The pre-test results showed that the target knowledge score regarding packaging and labels was 74.7, but this value increased to 88.7 during the post-test. This means that the target's knowledge increased after lectures and discussions were carried out during the activity. Evaluation of the level of target satisfaction with the implementation of the activity was carried out by filling out the satisfaction instrument. The result was a satisfaction score of 4.7 which means approaching very satisfied.